Corporate governance and disclosure practices of Ghanaian listed companies - Aboagye-Otchere, F.; Ossei-Kwakye, T. (Emerald Group Publishing Limited, 2012)
Purpose – The purpose of this study is to further increase the understanding of disclosure practices and the interrelationship between corporate governance (CG) and corporate disclosure (CD) of firms on the Ghana Stock Exchange (GSE). Design/methodology/approach – The study follows the trinary procedure of Aksu and Kosedag and uses Standard & Poor's T&D items in the construction disclosure index. Audit committee (AC) characteristics are the governance attributes. The study used a random effect panel regression analysis to establish the relationship between CD and CG of 20 listed companies covering a period from 2003‐2007. Findings – The results indicate that although there has been improvement of disclosure practices over the years, the level of disclosure in Ghana is moderate/fair. The study also documents a significant positive relationship between the presence of accounting/finance expert(s) on the ACs and CD practices. Originality/value – In spite of numerous researches on companies on the GSE, this paper is the first in the country that considers the impact of CG characteristics on disclosure practices.
Keywords: Ghana; Public companies; Corporate governance; Disclosure; Transparency; Audit committees